Pengembangan Media Pembelajaran Kosakata Bahasa Arab dengan Permainan My Happy Route di Sekolah Dasar - Ahmad, Alaudin; Muhlis, Nur Khozim; Fathih, Muhammad Amin (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Vocabulary learning that is called mufradat in Arabic demands teacher creativity in presenting innovations that accommodate increased learning outcomes. However, the fact is that mufradat learning in Raudhatul Qur’an Elementary School is not on target, so researchers see the need for learning innovations using the Happy Route which aims to accommodate the ability to memorize vocabulary. The aims of this research are to develop media through the game of my happy route at the Raudhatul Qur’an school and measure its effectiveness. This study uses the Research and Development (R&D) Borg and Gall model. The procedure uses 8 stages, namely: Potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage test. The results of this study indicate that the development of the Happy Route game is carried out by product design, content development, feasibility testing, field trials and product finalization. The results of the feasibility test showed that the products created and designed by the researchers were suitable for use as learning media due to an increase in the score from the pretest, which averaged 80 to the post-test, to an average of 94.4. Through this product, children become enthusiastic about learning and memorizing vocabulary according to their material.